Highly Oriented Nanowire Thin Films with Anisotropic Optical Properties Driven by the Simultaneous Influence of Surface Templating and Shear Forces - Probst, Patrick T.; Sekar, Sribharani; Koeng, Tobias A. F.; Formanek, Petr; Decker, Gero; Fery, Andreas; Pauly, Matthias (ACS Applied Materials and Interfaces, 2018)
The functional properties of nanoparticle thin films depend strongly on the arrangement of the nanoparticles within the material. In particular, anisotropic optoelectronic properties can be achieved through the aligned assembly of 1D nanomaterials such as silver nanowires (AgNWs). However, the control of the hierarchical organization of these nanoscale building blocks across multiple length scales and over large areas is still a challenge. Here, we show that the oriented deposition of AgNWs using grazing incidence spraying of the nano-object suspensions on a substrate comprising parallel surface wrinkles readily produces highly oriented monolayer thin films on macroscopic areas (>5 × 5 mm2). The use of textured substrates enhances the degree of ordering as compared to flat ones and increases the area over which AgNWs are oriented. The resulting microscopic linear arrangement of AgNWs evaluated by scanning electron microscopy (SEM) reflects in a pronounced macroscopic optical anisotropy measured by conventional polarized UV-vis-NIR spectroscopy. The enhanced ordering obtained when spraying is done in the same direction as the wrinkles makes this approach more robust against small rotational offsets during preparation. On the contrary, the templating effect of the wrinkle topography can even dominate the shear-driven alignment when spraying is performed perpendicular to the wrinkles: the concomitant but opposing influence of topographic confinement (alignment along the wrinkles) and of spray-induced shear forces (orientation along the spraying direction) lead to films in which the predominant orientation of AgNWs gradually changes from one direction to its perpendicular one over the same substrate in a single processing step. This demonstrates that exploiting the subtle balance between shear forces and substrate-nanowire interactions mediated by wrinkles offers a new way to control the self-assembly of nanoparticles into more complex patterns.
CRIS-Team Scopus Importer:2022-04-14
Keywords: anisotropic optical properties; nanowire; oriented assembly; spray coating; thin films; wrinkles